Nutritional Supplements Containing Cardus mariano, Eucalyptus globulus, Gentiana lutea, Urtica urens, and Mallotus philippinensis Extracts Are Effective in Reducing Egg Shedding in Dairy Jennies (Equus asinus) Naturally Infected by Cyathostomins - Arfuso, Francesca; Bazzano, Marilena; Brianti, Emanuele; Gaglio, Gabriella; Passantino, Annamaria; Tesei, Beniamino; Laus, Fulvio (Frontiers in Veterinary Science, 2020)
The increasing levels of anthelmintic resistance together with the restrictions in the use of drugs in food producing animals have enforced the search for sustainable alternative approaches for parasite control. The current study aimed to investigate the safety and the efficacy of a commercially available phytotherapic formulation against gastrointestinal strongyles in donkeys. Twenty-two Ragusana jennies (2.6 ± 0.5 years old) were assigned to two equal groups. One group was treated with two doses of a phytotherapic supplement Paraxitebio® containing Cardus mariano, Eucalyptus globulus, Gentiana lutea, Urtica urens, Mallotus philippinensis, 14 days apart (Group A). One group was used as negative control (Group B). Individual faecal samples were collected at the beginning of the study (T-1), and after 7, 14 and 28 days (T7, T14, T28). Blood samples were collected on T-1 and T28 in order to assess changes in donkeys’ haematological profile. After the initial rise in EPG values observed on T7, Group A showed a significant EPG decrease with lower eggs per gram (EPG) count compared to Group B on T28 and an overall faecal egg count reduction of 56.9% on the same time-point. Haematological parameters were within the normal physiological ranges for enrolled donkeys. However, significant differences in the values of RBCs, Hb, MCHC, MCV, WBCs, eosinophils and basophils were recorded between groups after phytotherapic treatments, with Group A showing a general improvement in the haemogram picture. The phytotherapic supplement used in the current study was helpful in controlling intestinal parasites allowing a significant reduction in the faecal egg count 28 days after treatment. Further studies are needed to better explore the specific mode of action of the plant-derived formulation herein tested as well as to encourage their use as tool for the control of equine strongylosis under multi-modal integrated approach in dairy donkey farms.